Modified Doppler Healthy Pregnancy Monitoring (MODEM-KES) to speed up examinations of pregnant women - Cory’ah, Fitra Arsy Nur; Suseno, Mutiara Rachmawati; Faiqah, Syajaratuddur; Megantari, Ayu Dini; Amrinsani, Farid (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2025)
Monitoring fetal health is a major factor in ensuring a healthy pregnancy and safe delivery. However, in Indonesia, especially in remote areas, limited access to quality health services, lack of sophisticated medical equipment, and difficulty reaching health facilities are serious challenges that contribute to high maternal and infant mortality rates. This study developed MODEM-KES (Modified Doppler Healthy Pregnancy Monitoring) which aims to evaluate the effectiveness of MODEM-KES in supporting health workers, especially midwives in remote areas, in conducting pregnancy monitoring more practically, accurately, and quickly. This tool integrates three important indicators: gestational age estimation, fetal weight estimation, and fetal heart rate, using Doppler sensors and fundus uteri height (FUH) measurements combined with digital methods. The research method involved testing the MODEM-KES prototype against standard tools, such as metline for FUH measurement and Doppler for FHR, with five measurements on each respondent with a gestational age of 26-40 weeks. Results showed that the difference in results between MODEM-KES and standardized tools was relatively small: FUH had a difference of 0-3 cm with an error rate of 0%-10.75%, FHR had a difference of -4/min to 4/min with an error rate of -3.0%-3.1%, and estimated fetal weight had a difference of 0-465 grams with an error rate of 0%-18.8%. Although the accuracy rate varies, MODEM-KES still shows potential as an alternative pregnancy monitoring tool that is practical and easy to use.